ATM cell delay and loss for best-effort TCP in the presence of isochronous traffic. - Tipper, C.B.
This paper reports the findings of a simulation study of the queueing behavior of ?best-effort? traffic in the presence of constant bit-rate and variable bit-rate isochronous traffic. In this study, best-effort traffic refers to ATM cells that support communications between host end systems executing various applications and exchanging information using TCP/IP. The performance measures considered are TCP cell loss, TCP packet loss, mean cell queueing delay, and mean cell queue length. Our simulation results show that, under certain conditions, best-effort TCP traffic may experience as much as 2% cell loss. Our results also show that the probability of cell and packet loss decreases logarithmically with increased buffer size
Keywords: ATM cell delay; ATM cell loss; TCP cell loss; TCP packet loss; TCP/IP.; Best-effort TCP; Cell loss probability; Constant bit-rate isochronous traffic; Host end systems; Mean cell queue length; Mean cell queueing delay; Packet loss probability; Performance measures; Queueing behavior; Simulation results; Simulation study; Variable bit-rate isochronous traffic